Scale‐free functional brain dynamics during recovery from sport‐related concussion. Issue 10 (29th April 2020) - Churchill, Nathan W.; Hutchison, Michael G.; Graham, Simon J.; Schweizer, Tom A.
Abstract: Studies using blood‐oxygenation‐level‐dependent functional magnetic resonance imaging (BOLD fMRI) have characterized how the resting brain is affected by concussion. The literature to date, however, has largely focused on measuring changes in the spatial organization of functional brain networks. In the present study, changes in the temporal dynamics of BOLD signals are examined throughout concussion recovery using scaling (or fractal) analysis. Imaging data were collected for 228 university‐level athletes, 61 with concussion and 167 athletic controls. Concussed athletes were scanned at the acute phase of injury (1–7 days postinjury), the subacute phase (8–14 days postinjury), medical clearance to return to sport (RTS), 1 month post‐RTS and 1 year post‐RTS. The wavelet leader multifractal approach was used to assess scaling ( c 1 ) and multifractal ( c 2 ) behavior. Significant longitudinal changes were identified for c 1, which was lowest at acute injury, became significantly elevated at RTS, and returned near control levels by 1 year post‐RTS. No longitudinal changes were identified for c 2 . Secondary analyses showed that clinical measures of acute symptom severity and time to RTP were related to longitudinal changes in c 1 . Athletes with both higher symptoms and prolonged recovery had elevated c 1 values at RTS, while athletes with higher symptoms but rapid recovery had reduced c 1 at acute injury. This study provides the first evidence for long‐term recovery of BOLD scale‐free brain dynamics after a concussion.